The Effects of Performance Budgeting and Funding Programs on Graduation Rate in Public Four-Year Colleges and Universities - Shinn, Jung-cheol; Milton, Sande (Education Policy Analysis Archives, 2004)
This study was conducted to determine whether states with performance budgeting and funding (PBF) programs had improved institutional performance of higher education over the five years (1997 through 2001) considered in this study. First Time in College (FTIC) graduation rate was used as the measure of institutional performance. In this study, the unit of analysis is institution level and the study population is all public four-or-more-year institutions in the United States. To test PBF program effectiveness, Hierarchical Linear Modeling (HLM) growth analysis was applied. According to the HLM analysis, the growth of graduation rates in states with PBF programs was not greater than in states without PBF programs. The lack of growth in institutional graduation rates, however, does not mean that PBF programs failed to achieve their goals. Policy-makers are advised to sustain PBF programs long enough until such programs bear their fruits or are proven ineffective.